Bipolar disorder course, impaired glucose metabolism and antioxidant enzymes activities: A preliminary report. (September 2016) - Mansur, Rodrigo B.; Rizzo, Lucas B.; Santos, Camila M.; Asevedo, Elson; Cunha, Graccielle R.; Noto, Mariane N.; Pedrini, Mariana; Zeni-Graiff, Maiara; Gouvea, Eduardo S.; Cordeiro, Quirino; Reininghaus, Eva Z.; McIntyre, Roger S.; et al.
Abstract: This study aimed to examine the role of oxidative stress in bipolar disorder (BD) by evaluating the relationship among antioxidant enzymes activities, impaired glucose metabolism (IGM) and illness course. We measured the activities of plasma superoxide dismutase (SOD) and glutathione peroxidase (GPx) in individuals with BD (N = 55) and healthy controls (N = 28). Information related to current and past psychiatric/medical history, as well as prescription of any pharmacological treatments was captured. Impaired glucose metabolism was operationalized as pre-diabetes or type 2 diabetes mellitus. Our results showed that, after adjustment for age, gender, alcohol use, smoking and current medication, both BD (p < 0.001) and IGM (p = 0.019) were associated with increased GPx activity, whereas only BD was associated with decreased SOD activity (p = 0.008). We also observed an interaction between BD and IGM on SOD activity (p = 0.017), whereas the difference between BD and controls was only significant in individuals with IGM (p = 0.009). IGM, GPx and SOD activity were independently associated with variables of illness course. Moreover, IGM moderated the association between SOD activity and number of mood episodes (p < 0.001), as a positive correlation between SOD activity and mood episodes was observed only in participants with IGM. In conclusion, BD and IGM are associated with independent and synergistic effects on markers of oxidative stress. The foregoing observations suggest that the heterogeneity observed in previous studies evaluating antioxidant enzymes in BD may be a function of concurrent IGM; and that imbalances in the oxidative system may subserve the association between BD and IGM, as well as its relationship with illness course.